BUSINESS MODEL INNOVATION FOR PT. CASAMIRAH BANGUN INDONESIA TO OVERCOME COMPANY UNSTABLE INCOME (The Indonesian Journal of Business Administration, 2019)
Starting as an individual business in 2012, Casamirah is an interior contractor and design company, work mostly at of food & beverage sector, such as projects for cafes and restaurants. Since 2016, corporate clients’ contributions have been dominating the total revenue of the company. Almost all the corporate clients have been returning customers and contributed significantly to Casamirah’s business. In the current business model, Casamirah main activity is as an interior contractor and design. Company main revenue is depending on how the company win over the big contract and how the project manager and all the supporting division performance to deliver the project according the budget and time agreement. These condition is contributed to company unstable cash flowThis research is conducted to find the solution of this problem. Internal and external environment company analysis have been conducted using several tools, there are PEST analysis, Porter’s Five Forces, Porter’s Generic Value Chain Model, VRIO framework and Existing Business Model Canvas. Semi-structure interview also conducted to identify and analyze the company problems and how to utilize Casamirah elements to solve the problem.Eventually the root cause of the problem is identified, i.e., lack of bargaining in corporate agreement, less marketing activities and lack of knowledge in project acquisition and development. In addressing those problem, business model innovation based on offer-driven innovation is formulated. Three relevant strategic actions are recommended for Casamirah, they are product innovation (sharing workshop & material distributor), digital marketing and social media campaign, and employee training and development program. Positives impact are expected from this strategic actions, in terms of generating new revenue sources and stabilizing company’s cash flow due to developed key activities and product innovation. The implementation of these actions is also expected to improving employee knowledge and competence due to the training and development program.Keywords: business model innovation, interior contractor, unstable cash flow